Analysing a system of systems characterisation to define system of systems engineering practices. (3rd December 2009) - Meentemeyer, Scott M.; Sauser, Brian; Boardman, John
Even though there is no clear accepted definition for SoS, the term is widely recognised and typically refers to large-scale or complex systems that provide a set of capabilities. Since SoS is still a fairly infant field, there is also much discussion on the tools, methodologies, thought processes and analysis used to design these massive systems. The purpose of this paper is to describe five distinguishing characteristics that have been proposed for describing an SoS. It is believed that by realising these characteristics one may gain insight into the nature of an SoS and develop a deeper appreciation of the SoS. An example of an SoS is provided and discussed. In addition, this paper will look at principles, strategies and approaches that may be used when working on an SoS engineering project with the intent of suggesting concepts that might become part of an SoS course.